Emerson from an Indian Point of View - Maitra, Herambachandra (Harvard theological review, 1911)
Of the eminent writers who are the exponents of the spiritual movement of the nineteenth century, those whose influence is most widely acknowledged—Wordsworth, Shelley, Carlyle, Emerson—have two notable characteristics: first, they either give a very subordinate place to dogma or reject it altogether; secondly, they lay great stress on truths which from remote antiquity have most deeply impressed the Oriental mind and have been uttered with the greatest power in the East. The influence of Wordsworth as a spiritual teacher will ever be felt, in spite of the “Ecclesiastical Sonnets,” to lie, not in his championship of orthodox Christianity, but in his awakening men to a sense of the Infinite revealed in the finite and to a consciousness of the immanence of the divine Spirit in the outer and the inner world. These are the truths which inspire some of Shelley's noblest lines. They find utterance in Carlyle's wisest words. And they occupy the foremost place in Emerson's message to an unspiritual world. Hence the power with which Wordsworth and Emerson appeal to the Oriental mind. They translate into the language of modern culture what was uttered by the sages of ancient India in the loftiest strains. They breathe a new life into our old faith, and they assure its stability and progress by incorporating with it precious truths revealed or brought into prominence by the wider intellectual and ethical outlook of the modern spirit. Before I dwell at any length on the spiritual affinity between the teachings of the East and the mind of Emerson, it will be convenient to consider some of his intellectual traits, which give us a key to the right interpretation of his faith.